USB Learning Module - Mathews, Praveen Manaprath (Universiti Teknologi Petronas, 2008)
In Universiti Teknologi Petronas (UTP), it is essential for Electrical and Electronic engineering students to grasp the basis of C programming. Quite often, programming is taught through lectures and the lab exercises are more computer science related rather than Electrical and Electronic. Thus the main objective of this project is to produce course materials to aid in the teaching of programming in UTP. The main feature of these course materials will be a PIC microcontroller board and several interface modules. The PIC microcontroller board communicates with the PC via the USB port. Example worksheets are also produced to facilitate the teaching and learning process.